Influence of Superplasticizer Dosage on Workability and Mechanical properties of Concrete made with Recycled Aggregate - Ashtar Al-Luhybi; Nuha H. Al-Jubory; Anas S. Ahmed (Institute for Research and Community Services, Institut Teknologi Bandung, 2022)
This study investigated the effect of adding a type of superplasticizer (polycarboxylate ether -PCE) on the workability and mechanical properties of concrete containing recycled coarse aggregate (RCA). The effect of increasing the PCE dosage while changing the water/cement ratio on RCA strength was also studied. To accomplish these goals, three groups of concrete mixtures were prepared. The variable in these groups was the water/cement ratio (0.53, 0.57, and 0.615). In each group, the natural aggregate was replaced by two proportions of RCA (50 and 100%) and different proportions of PCE were added for each replacement ratio. The findings encourage the use of PCE in recycled concrete. It was found that the addition of PCE improves the properties of recycled concrete in terms of workability and compactness. The addition of PCE also compensates for the compressive strength that is lost due to the replacement of natural aggregate with recycled coarse aggregate.